2015
DOI: 10.1016/j.snb.2015.07.091
|View full text |Cite
|
Sign up to set email alerts
|

Trends in microfluidic systems for in situ chemical analysis of natural waters

Abstract: Spatially and temporally detailed measurement of ocean, river and lake chemistry is key to fully understanding the biogeochemical processes at work within them. To obtain these valuable data, miniaturised in situ chemical analysers have recently become an attractive alternative to traditional manual sampling, with microfluidic technology at the forefront of recent advances. In this short critical review we discuss the role, operation and application of in situ microfluidic analysers to measure biogeochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 75 publications
0
77
0
Order By: Relevance
“…Both instruments were also thoroughly evaluated as part of the Alliance for Coastal Technologies efforts (http://www.act-us.info/). A more comprehensive review of aquatic chemical sensors can be found in Beaton et al (2012), Rerolle et al (2013), Nightingale et al (2015), or Bagshaw et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Both instruments were also thoroughly evaluated as part of the Alliance for Coastal Technologies efforts (http://www.act-us.info/). A more comprehensive review of aquatic chemical sensors can be found in Beaton et al (2012), Rerolle et al (2013), Nightingale et al (2015), or Bagshaw et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical reagentless sensors, which hold great promise for long-term unattended operations on fixed and mobile platforms, have recently been developed (JoƄca et al, 2011(JoƄca et al, , 2013bBarus et al, 2016), but require further development and extensive field testing prior to use during field campaigns. By virtue of their robustness, low reagent and power consumption (1.8 W), ability to store waste onboard and to operate using established chemical protocols in a miniaturized manifold, microfluidic Lab-On-Chip sensors are well-suited to in situ monitoring in natural waters (Beaton et al, 2012;Nightingale et al, 2015;YĂŒcel et al, 2015). In a companion paper, Clinton-Bailey et al (2017) described a prototype phosphate LOC sensor and its application to in situ monitoring in a UK chalk stream.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic chips now are employed in the fields of chemistry, physics, biology, medicine, agriculture, food, and environmental monitoring . Among them, applications in biomedical research and related fields are the most widely and thoroughly studied.…”
Section: Microfluidicsmentioning
confidence: 99%